Synthesis, Biological Evaluation and Docking Studies of Sorafenib Derivatives N-(3-fluoro-4-(pyridin-4-yloxy)phenyl)-4(5)-phenylpicolinamides - Wang, Min; Wu, Chunjiang; Xu, Shan; Zhu, Yan; Li, Wei; Zheng, Pengwu; Zhu, Wufu (Medicinal Chemistry, 2017)
Background: Sorafenib is an important VEGFR2/KDR inhibitor which is widely used for the treatment of cancer. Objective: In this paper, two series of sorafenib analogues N-(3-fluoro-4-(pyridin-4-yloxy)phenyl)-4- phenylpicolinamides(13a–k) and N-(3-fluoro-4-(pyridin-4-yloxy)phenyl)-5-phenylpicolinamides (14a–k) were designed and synthesized. Methods: Their structures were confirmed by various analytical methods, such as 1 H and 13 C NMR, m.p., MS, HRMS. All of them were evaluated for IC50 values against three cancer cell lines (A549, PC-3 and MCF-7). Results: Eleven of the synthesized compounds showed moderate to excellent cytotoxicity activity against different cancer cells, whose potency from single-digit μM to nanomolar range. And five of them were equal to more potent than sorafenib against one or more cell lines. The most promising compound 14c showed excellent antitumor activities against PC-3 and MCF-7 cell lines with IC50 values of 2.62±1.07 μM and 1.14±0.92 μM, which were 1.15 to 2.75-fold more active than sorafenib (3.03±1.01 μM, 3.14±1.65 μM), respectively. Conclusion: Structure-activity relationships (SARs) and docking studies indicated that the replacement of diarylurea of sorafenib with phenylpicolinamide moiety benefited to the activity. The position of aryl group and the substituents of aryl group had a great influence on antitumor activity and selectivity. The aryl groups with the substitute of alkyl groups (-CH3), halogen atoms (-F,Cl) were favorable to the cytotoxicity. However, this series of compounds showed moderate activity against VEGFR2/KDR kinase. Mechanism of target compounds was not quite clear and further study will be carried out to identify the possible target.
Keywords: sorafenib